Electromagnetic Radiations: A Possible Impact on Population of House Sparrow (Passer Domesticus) - Shende, Virendra Abaji; Patil, Kishor G. (Engineering International, 2015)
The modern world is a full of contamination of radiofrequency (RF), “electrosmog” in the urban centers especially after the rapid introduction of mobile telecommunications systems. The aim of this study is to determine the impact on population of house sparrow, Passer domesticus by electromagnetic radiation (microwaves) from phone antennae. By monthly monitoring in urban and rural area, it is found that the population of house sparrow is declining in the urban area, where cell phone towers are more as compared to the rural area in every season.